Analisis Penawaran Perspektif Ekonomi Islam: Peran Kejujuran, Biaya Produksi, Regulasi Pemerintah, Dan Kesadaran Halal Produsen - Eza Okhy Awalia Br Nasution; Melia Sari; Angga Putra Suhadi; Syahrul Abadi (CV. ITTC INDONESIA, 2026)
This article examines the concept of supply in Islamic microeconomics by emphasizing ethical and institutional dimensions that are frequently marginalized in conventional economic analysis. Instead of viewing supply merely as a technical response to price signals and production costs, Islamic economics places it within a broader framework of moral responsibility, social justice, and compliance with Sharia principles. Using a qualitative descriptive approach based on library sources, this article draws on classical and contemporary Islamic economic literature, peer reviewed journals, and relevant policy documents to analyze the roles of producer honesty, production costs, government regulation through the hisbah mechanism, and halal awareness in shaping supply behavior. The discussion shows that supply in Islamic economics is not determined solely by efficiency considerations and cost structures, but is also guided by ethical commitments that restrain exploitative practices such as excessive pricing, hoarding, and quality distortion. Honesty and halal compliance appear not only as moral obligations, but also as strategic elements that strengthen market trust and support business sustainability. Government intervention, meanwhile, is positioned as a corrective effort aimed at maintaining market balance and protecting public welfare without undermining market mechanisms. Overall, this article highlights that the integration of ethical values, economic rationality, and institutional oversight offers a more holistic and equitable understanding of supply, which remains highly relevant in addressing contemporary market challenges.